Layer-dependent excellent thermoelectric materials: from monolayer to trilayer tellurium based on DFT calculation - Zhang, Kexin; Yang, Rennong; Sun, Zhehao; Chen, Xihao; Huang, Sizhao; Wang, Ning (Frontiers in Chemistry, 2023)
Monoelemental two-dimensional (2D) materials, which are superior to binary and ternary 2D materials, currently attract remarkable interest due to their fascinating properties. Though the thermal and thermoelectric (TE) transport properties of tellurium have been studied in recent years, there is little research about the thermal and TE properties of multilayer tellurium with interlayer interaction force. Herein, the layer modulation of the phonon transport and TE performance of monolayer, bilayer, and trilayer tellurium is investigated by first-principles calcuations. First, it was found that thermal conductivity as a function of layer numbers possesses a robust, unusually non-monotonic behavior. Moreover, the anisotropy of the thermal transport properties of tellurium is weakened with the increase in the number of layers. By phonon-level systematic analysis, we found that the variation of phonon transport under the layer of increment was determined by increasing the phonon velocity in specific phonon modes. Then, the TE transport properties showed that the maximum figure of merit (ZT) reaches 6.3 (p-type) along the armchair direction at 700 K for the monolayer and 6.6 (p-type) along the zigzag direction at 700 K for the bilayer, suggesting that the TE properties of the monolayer are highly anisotropic. This study reveals that monolayer and bilayer tellurium have tremendous opportunities as candidates in TE applications. Moreover, further increasing the layer number to 3 hinders the improvement of TE performance for 2D tellurium.